Targeting mechanotransduction mechanisms and tissue weakening signals in the human amniotic membrane - Barrett, David W. (2019)
Mechanical and inflammatory signals in the fetal membrane play an important role in extracellular matrix (ECM) remodelling in order to dictate the timing of birth. We developed a mechanical model that mimics repetitive stretching of the amniotic membrane (AM) isolated from regions over the placenta (PAM) or cervix (CAM) and examined the effect of cyclic tensile strain (CTS) on mediators involved in mechanotransduction (Cx43, AKT), tissue remodelling (GAGs, elastin, collagen) and inflammation (PGE2, MMPs). In CAM and PAM specimens, the application of CTS increased GAG synthesis, PGE2 release and MMP activity, with concomitant reduction in collagen and elastin content. Co-stimulation with CTS and pharmacological agents that inhibit either Cx43 or AKT, differentially influenced collagen, GAG and elastin in a tissue-dependent manner. SHG confocal imaging of collagen fibres revealed a reduction in SHG intensity after CTS, with regions of disorganisation dependent on tissue location. CTS increased Cx43 and AKT protein and gene expression and the response could be reversed with either CTS, the Cx43 antisense or AKT inhibitor. We demonstrate that targeting Cx43 and AKT prevents strain-induced ECM damage and promotes tissue remodelling mechanisms in the AM. We speculate that a combination of inflammatory and mechanical factors could perturb typical mechanotransduction processes mediated by Cx43 signalling. Cx43 could therefore be a potential therapeutic target to prevent inflammation and preterm premature rupture of the fetal membranes.